Consumer Preferences for Fermented Foods in Majene Regency, West Sulawesi - Trinoviyani, Trinoviyani; Wakiah, Nurul; Fadillah, Ummu Farah (Jurnal Biologi Tropis, 2025)
Fermented foods are processed products with significant potential to enhance nutritional value and public health. This study aimed to investigate consumer preferences for fermented foods in Majene Regency, West Sulawesi, and to identify the factors influencing consumer choices. A total of 100 respondents were selected using Slovin's formula and surveyed through an online questionnaire. The results indicate that the consumption of fermented foods in Majene is still dominated by traditional products such as tempeh (86%) and tape (9%), which are predominantly obtained from traditional markets (91%). Consumer preferences were primarily influenced by taste and texture (65%), rather than health benefits (37%). Other influential factors included price (40%) and product availability (35%). The majority of respondents expressed a desire for traditional fermented products to be packaged in a more modern way (73%) and showed interest in new product innovations (91%). Key consumer expectations include increased awareness of health benefits (61%), more attractive packaging (32%), and flavor variety (20%). These findings highlight substantial opportunities for the development of local fermented foods through innovative approaches that preserve traditional values while meeting the expectations of modern consumers. The study offers strategic recommendations for businesses and policymakers in promoting nutrition education and fermented food product development in the Majene region.